2012
DOI: 10.1080/19338244.2011.578682
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Morbidity and Emotional Exhaustion Among Hospital Physicians and Nurses: Association With Perceived Job-Related Factors

Abstract: The objective of this study was to evaluate psychiatric morbidity and emotional exhaustion among physicians and nurses of a general hospital in central Italy, examining the association with perceived job-related factors. Anonymous questionnaires were distributed to all 323 hospital physicians and 609 nurses of a nonprofit health organization in Rome, Italy. Standardized instruments were used to evaluate psychiatric morbidity (General Health Questionnaire), burnout (Maslach Burnout Inventory), and perceived job… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 23 publications
3
33
2
3
Order By: Relevance
“…Furthermore, the overall NICU size, presence of trainees, institutional standards for physician presence, and medical record system may influence workloads and job satisfaction among different categories of providers. 10 The effect of organizational factors on NICU provider burnout is unknown. The objectives of this study were to:…”
Section: What This Study Addsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the overall NICU size, presence of trainees, institutional standards for physician presence, and medical record system may influence workloads and job satisfaction among different categories of providers. 10 The effect of organizational factors on NICU provider burnout is unknown. The objectives of this study were to:…”
Section: What This Study Addsmentioning
confidence: 99%
“…It seems likely that the absolute numbers of nursing hours per patient provide an incomplete description of the nursing workload that may contribute to burnout. 10,25 The development of an acuityadjusted nurse staffing metric would benefit future investigations of the associations between organizational factors and staff and patient outcomes.…”
Section: Figurementioning
confidence: 99%
“…In contrast to previous studies, physicians showed higher levels of EE, D, and lower levels of PA compared to the nurses in our study. 29,[31][32][33] Study of the Keeton and colleagues was to explore factors related with physician career satisfaction, work-life balance, and burnout in department of obstetrics and gynecology. 34 They found that burnout is an important predictor of career satisfaction, control over schedule, and work hours.…”
Section: Discussionmentioning
confidence: 99%
“…Para pengguna layanan kesehatan juga mengeluhkan penurunan kualitas pelayanan kesehatan yang diberikan perawat (Clausen et al, 2012, Schmidt dan Diestel, 2012 Karena sifat alamiah dari pekerjaannya, perawat merupakan kelompok tenaga kesehatan yang berisiko untuk mengalami burnout dibanding tenaga kesehatan lainnya (Lorenz et al, 2010). Studi terbaru menyimpulkan burnout pada perawat berhubungan dengan kelelahan emosional dan peningkatan morbiditas terkait dengan gangguan kejiwaan (Renzi et al, 2012). Selanjutnya Al Turki (2010) melaporkan tingkat prevalensi kelelahan emosional tinggi dan depersonalisasi disertai dengan rendahnya tingkat prestasi pribadi pada perawat berhubungan dengan burnout.…”
Section: Pendahuluanunclassified